Isolation of Simian Virus 40 Recombinants from Cells Infected with Oligomeric Forms of Simian Virus 40 Deoxyribonucleic Acid - Dubbs, Del Rose (1972)
Oligomeric forms of simian virus 40 (SV40) deoxyribonucleic acid (DNA) were isolated from monkey kidney cells infected with two plaque morphology mutants of SV40. Recombinant, large clear-plaque-type SV40 was produced in cells productively infected with oligomeric forms of SV40 DNA.